Evaluation of Oxidative Stress and DNA Damage Indicators Following A Long Period of Resistance Training in Sedentary Older Men - Javad Norouzi; Afsaneh Khosravi; Babak Hooshmand Moghadam; Abbas Ali Gaeini (Tehran University of Medical Sciences, 2021)
Background and Aim: Excessive production of free radicals and the accumulation of oxidative damages play an important role in accelerating the aging process. However, one of the ways to fight against aging and related diseases is through physical activity. The aim of the present study was to investigate the effect of 12 weeks of resistance training on oxidative stress indicators (8-iso-prostaglandin-F2α: 8-iso PGF2α) and oxidative DNA damage (8-hydroxydeoxyguanosine: 8-OHdG) in elderly men. Materials and Methods: In this quasi-experimental study, 30 elderly men were selected voluntarily and purposefully as a statistical sample and were randomly divided into experimental (n=15) and control (n=15) groups. Participants of the experimental group performed resistance exercises three sessions per week for 12 weeks. At the beginning and end of the study, serum levels of 8-iso PGF2α and 8-OHdG were measured by ELISA method. Correlated and independent t-tests were used to compare intragroup and intergroup means, respectively. Results: Serum values of 8-iso PGF2α (P=0.007) and 8-OHdG (P=0.013) decreased significantly after 12 weeks of resistance training. Also, there was a significant difference between the experimental and control groups in serum values of 8-iso PGF2α (P=0.009) and 8-OHdG (P=0.02). Conclusion: It seems that 12 weeks of resistance training reduces the values of oxidative stress (8-iso PGF2α) and oxidative DNA damage (8-OHdG) indicators in older men. Therefore, regular resistance training can play an important role in preventing injuries caused by oxidative stress, especially in old age.